Model Dinamik Paritas Suku Bunga Indonesia Menggunakan Error Correction Model - Elva Dona; antoni antoni; gina elmizan (JURNAL PUNDI, 2017)
The purchasing power parity doctrine in determining exchange rate changes focuses on  price factor changes (Jiang, Li, Chang, & Su, 2013)This study examines how currency and interest rates interact with each other to achieve a balance position in the foreign exchange market.Through this approach the exchange rate is determined by the balance of demand and supply between two currencies. This approach also explains how the influence of economic variables such as money supply, national income, price level, and interest rate on the formation of currency rates. Data using  the first quarter of 2000 through the fourth quarter of 2013, With econometric analysis through cointegration approach and Error Correction Model will be tested the validity of interest rate parity condition in Indonesi.Estimation of the error correction model variable (V), indicating that the variable passed the t test at 5% confidence level. It indicates that the models specification is acceptable and there is cointegration between the observed variables.